Molecular beam epitaxial growth of high quality Ga-catalyzed GaAs1–xSbx(x > 0.8) nanowires on Si (111) with photoluminescence emission reaching 1.7 μm. (25th October 2018) - Deshmukh, Prithviraj; Sharma, Manish; Nalamati, Surya; Reynolds, C Lewis; Liu, Yang; Iyer, Shanthi
Abstract: The advancement of ternary GaAsSb mismatched alloy system toward the Sb-rich corner of the phase diagram in the nanowire (NW) configuration on silicon remains a challenge. A large lattice mismatch between the silicon substrate and GaAsSb with an Sb-rich composition, along with the low supersaturation and low solubility of Sb in the Ga droplet in the vapor–liquid–solid growth mechanism, causes significant issues during Ga-assisted molecular beam epitaxial growth of these NWs. In this work, we have carried out a systematic study of Sb-rich GaAs1– x Sb x NWs grown on Si (111) using variations of the Ga, As, and Sb beam equivalent pressures (BEP) to minimize undesirable parasitic growth and achieve photoemission up to 1.7 μ m. Ga-assisted molecular beam epitaxy is the enabling growth technology for the growth of these self-catalyzed GaAs1– x Sb x ( x  > 0.8) NWs. The use of a dual substrate temperature approach along with low As background pressure and a low Ga BEP were found to be the key growth components in achieving a well-faceted NW morphology with a low parasitic layer on the substrate. Energy-dispersive x-ray spectroscopy analysis confirms uniform compositional homogeneity along the NWs, while selected-area electron diffraction patterns in the transmission electron microscope revealed a zinc-blende crystal structure. A peak μ -photoluminescence emission of 1680 nm with a narrow FWHM was obtained at 4 K. Raman spectra at room temperature exhibit only GaSb related LO and TO modes, which attest to the high quality of the NWs grown. This is a promising approach due to the broad scope of applicability to grow other mismatched alloy material systems in a NW configuration.